The Risk of Adverse Drug-Drug Interactions for Stable Angina Pectoris Patients with Heart Failure Complication Prescribed Polypharmacy - Fadillah, Ahmad Aldi; Bakhriansyah, Mohammad; Yustikasari, Intan; Nurikhwan, Pandji Winata; Adiputro, Dwi Laksono (Berkala Kedokteran, 2023)
Stable angina pectoris (SAP) is an imbalance that occurs when myocardial oxygen need increases disproportionally, causing complaints of chest pain. Uncontrolled SAP can lead to a complication of heart failure (HF). Polypharmacy treatment frequently given to SAP patients with HF complications can be potentially detrimental for them. This study aims to determine the risk of adverse drug-drug interactions in SAP patients with HF complications prescribed polypharmacy. This was an analytic observational study with a cross-sectional approach using retrospective data from medical record data from 2020-2021 among hospitalized patients in cardiology ward Ulin General Hospital, Banjarmasin. Potential drug-drug interactions were determined using the Lexicomp tool from the UpToDate® site. Prevalence Odds Ratio (POR) and 95% Confidence Interval (95%CI) were determined using the Logistic Regression test at the 95% level of confidence. Twenty-four SAP patients with HF were recruited. According to its potential interactions, the most interactions were under category C (82.6%), followed by category B (11.3%) and category D (6.0%). Based on its level of severity, the most common was moderate (77.4%), followed by minor (13.0%) and major (9.5%). SAP patients with HF who were not prescribed polypharmacy had a lower risk of adverse drug-drug interactions by 64.7% compared to polypharmacy users, although it was not statistically difference (crude POR 0.353, 95% CI; 0.360-3.421; p-value = 0.369). This study shows that there is a tendency of lower risk of adverse drug-drug interactions in SAP patients with HF complication prescribed polypharmacy compared to those without polypharmacy, but the association is not statistically significant.